Deformable image registration uncertainty for inter-fractional dose accumulation of lung cancer proton therapy. (June 2020) - Nenoff, Lena; Ribeiro, Cássia O.; Matter, Michael; Hafner, Luana; Josipovic, Mirjana; Langendijk, Johannes A.; Persson, Gitte F.; Walser, Marc; Weber, Damien Charles; Lomax, Antony John; Knopf, Antje-Christin; Albertini, Francesca; et al.
Highlights: Dose degradations caused by anatomy are larger than DIR uncertainties. Averaged results from several DIRs provide a good representation of dose degradation. We caution the use of only one DIR algorithm for dose accumulation. Abstract: Background and purpose: Non-small cell lung cancer (NSCLC) patients show typically large anatomical changes during treatment, making recalculation or adaption necessary. For report and review, the applied treatment dose can be accumulated on the reference planning CT using deformable image registration (DIR). We investigated the dosimetric impact of using six different clinically available DIR algorithms for dose accumulation in presence of inter-fractional anatomy variations. Materials and methods: For seven NSCLC patients, proton treatment plans with 66 Gy-RBE to the planning target volume (PTV) were optimised. Nine repeated CTs were registered to the planning CT using six DIR algorithms each. All CTs were acquired in visually guided deep-inspiration breath-hold. The plans were recalculated on the repeated CTs and warped back to the planning CT using the corresponding DIRs. Fraction doses warped with the same DIR were summed up to six different accumulated dose distributions per patient, and compared to the initial dose. Results: The PTV-V95 of accumulated doses decreased by 16% on average over all patients, with variations due to DIR selection of 8.7%. A separation of the dose effects caused by anatomical changes and DIR uncertainty showed a good agreement between the dose degradation caused by anatomical changes and the dose predicted from the average of all DIRs (differences of only 1.6%). Conclusion: The dose degradation caused by anatomical changes was more pronounced than the uncertainty of employing different DIRs for dose accumulation, with averaged results from several DIRs providing a good representation of dose degradation caused by anatomy. However, accumulated dose variations between DIRs can be substantial, leading to an additional dose uncertainty.